Growth and feeding in the sponge Agelas tubulata from shallow to mesophotic depths on Grand Cayman Island. Issue 9 (26th September 2021) - Macartney, Keir J.; Clayshulte Abraham, Amelia; Slattery, Marc; Lesser, Michael P.
Abstract: On Caribbean coral reefs, sponges are important members of the benthic community and play multiple roles in ecosystem structure and function. They have an important role in benthic‐pelagic coupling, consuming particulate organic matter (POM) and dissolved organic matter (DOM) and in turn providing food in the form of sponge biomass or the release of detritus for a variety of coral reef organisms. Throughout the Caribbean, sponges show consistent increases in their abundance and growth rates as depth increases into the mesophotic zone (30–150 m). This has been hypothesized to be driven by bottom‐up forces, particularly the increased supply of nitrogen‐rich POM in mesophotic coral reef ecosystems (MCEs). Here, we tested the hypothesis that the sponge, Agelas tubulata, exhibits increased growth rates on MCEs relative to shallow reefs on Grand Cayman Island and that this is driven by bottom‐up forcing. We observed increased growth rates in mesophotic A. tubulata, compared with shallow conspecifics, despite variability in feeding on both POM and DOM. Mesophotic sponges, however, were consistently exposed to greater amounts of POM, which was seasonally variable unlike DOM. Changes in stable isotopic signatures, and higher feeding rates with increasing depth, were consistent with increasing rates of growth in sponges as depth increases. These observations support the hypothesis that mesophotic sponges have higher growth rates due to increased POM availability and consumption over time. The results of this study illustrate the crucial role that bottom‐up forcing has in the structuring of sponge communities on both shallow and mesophotic Caribbean coral reefs and the importance of POM as a source of nitrogen in sponge diets.